DEVELOPING AN ECOPEDAGOGICAL THEMATIC LEARNING MODEL TO ENHANCE ENVIRONMENTAL LITERACY IN PRIMARY EDUCATION - Nugraha, Mohammad Fahmi; Nadiroh, Nadiroh; Artanti, Guspri Devi (LPPM Universitas Jambi, 2026)
Global environmental issues require early educational interventions; however, environmental education in primary schools is still predominantly cognitive-oriented and has not effectively fostered students’ attitudes and behaviors. This study aims to develop and examine the effectiveness of an ecopedagogical thematic learning model to enhance environmental literacy. This research employed a Research and Development (R&D) approach based on the Dick and Carey model. The participants were 75 upper-grade primary school students in Tasikmalaya, Indonesia, selected through simple random sampling. Data were collected through observation, interviews, and validated instruments, and analyzed using descriptive statistics, the Wilcoxon signed-rank test, and normalized gain (N-gain). The results show that the developed model is highly feasible (mean = 4.70) and received very positive student responses (93.33%–96.26%). Statistical analysis indicates a significant improvement in students’ environmental literacy (p < .001), with an average N-gain score of 0.62, categorized as moderate to high. The novelty of this study lies in the integration of ecopedagogical principles, thematic learning, and experiential learning into a structured instructional model that simultaneously addresses cognitive, affective, and behavioral domains. These findings imply that the model can be used by teachers as a holistic and student-centered approach to design more meaningful and sustainability-oriented learning in primary education.